ASSESSMENT OF THE FUNCTIONAL STATE OF PATIENTS (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The assessment of a patient's functional state is a cornerstone of modern clinical practice, serving as a critical determinant for diagnosis, treatment planning, and prognostic evaluation. This article explores the multifaceted approach to evaluating functional capacity, encompassing physiological parameters, physical performance, and psychological well-being. It highlights the importance of utilizing both objective clinical metrics-such as cardiovascular and respiratory stress tests-and subjective patient-reported outcome measures. By integrating standardized assessment tools and scales, healthcare providers can obtain a comprehensive profile of a patient’s ability to perform activities of daily living.
Keywords: Functional assessment, patient monitoring, clinical indicators, physical capacity, diagnostic tools, quality of life, activities of daily living, prognostic evaluation, rehabilitation, physiological status.